PENGARUH KOMPETENSI, MOTIVASI, KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BNN PROVINSI SULAWESI UTARA - Pandensolang, Fatrisye; Olivia S. Nelwan; Jessy J. Pondaag (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
ABSTRACT: This study aims to analyze the influence of competence, motivation, leadership, and work environment on job satisfaction and employee performance, with job satisfaction as a mediating variable at the National Narcotics Board (BNN) of North Sulawesi Province. This research employs a quantitative explanatory method using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) approach. Data were collected through questionnaires distributed to all employees of BNN North Sulawesi Province and processed using SmartPLS software. The results indicate that motivation and work environment have a positive and significant effect on job satisfaction, while competence and leadership have no significant effect on job satisfaction. Furthermore, competence and job satisfaction significantly affect employee performance, whereas motivation, leadership, and work environment show no direct effect. However, job satisfaction significantly mediates the relationship between motivation and work environment with performance, but not between competence or leadership and performance. These findings confirm that job satisfaction plays a crucial psychological mediating role linking individual and environmental factors to employee performance. Intrinsic motivation, a supportive work environment, and emotionally engaged leadership are proven to enhance performance more effectively than structural control alone. Theoretically, the study reinforces Herzberg’s, Locke’s, and Spencer’s frameworks in the public-sector context and contributes an empirical model of satisfaction-based employee performance, which is highly relevant for government institutions such as National Narcotics Board (BNN) North Sulawesi.